The Bielski brothers : the true story of three men who defied the Nazis, built a village in the forest, and saved 1,200 Jews - Duffy, Peter, 1969- (New York : Perennial, 2004)
In 1941, three brothers witnessed their parents and two other siblings being led away to their eventual murders. It was a grim scene that would, of course, be repeated endlessly throughout the war. Instead of running or giving in to despair, these brothers -- Tuvia, Zus, and Asael Bielski -- fought back, waging a guerrilla war of wits against the Nazis. By using their intimate knowledge of the dense forests surrounding the Belarusan towns of Novogrudek and Lida, the Bielskis evaded the Nazis and established a hidden base camp, then set about convincing other Jews to join their ranks. As more and more Jews arrived each day, a robust community began to emerge, a "Jerusalem in the woods." In July, after two and a half years in the woods the Bielskis learned that the Germans, overrun by the Red Army, were retreating back toward Berlin. More than one thousand Bielski Jews emerged -- alive -- on that final, triumphant exit from the woods. But as nororitey grew, so too did the Nazi efforts to capture the rugged brothers and on several occasions they came so near to succeding that the Bielskis had to abandon the camp and lead their massive entourage to newer, safer locaitons. And while some argued in favor of a smaller, more mobile unit, focused strictly on waging battle against the Germans, Tuvia Bielski was firm in his commitment to all Jews. "I'd rather save on old Jewish woman, " he said, "than kill ten Nazis."
Includes bibliographical references (p. [281]-297).
Keywords: Bielski, Asael; Bielski, Tuvia; Bielski, Zus, -- 1912-1995.; Jews -- Persecutions -- Belarus; Holocaust, Jewish (1939-1945) -- Belarus; World War, 1939-1945 -- Jewish resistance -- Belarus; World War, 1939-1945 -- Jews -- Rescue -- Belarus